Task values and self‐efficacy beliefs of undergraduate psychology students. (11th May 2016) - Green, Rebecca A.; Conlon, Elizabeth G.; Morrissey, Shirley A.
Abstract: Objective: Psychological literacy has been proposed as an outcome for psychology graduates, which requires an understanding of and integration between theory, research, and practice. Using the expectancy‐value theory, the current study aimed to examine psychology students' values and self‐efficacy towards these domains. Method: Three hundred and nineteen psychology students ( M age = 26.25, SD = 10.26) reported on their social influences, task values, and self‐efficacy beliefs for theory, research, and practice. Results: Using 3 (Year) × 3 (Domain) mixed factorial analyses of variance (ANOVAs), it was shown that students have poorer task values and lower self‐efficacy towards research than theory or practice. A consistent effect of year was not found for task values, but students' self‐efficacy beliefs showed an effect of training, with first years reporting poorer self‐efficacy than middle and fourth‐year students. Results indicated that students hold contrasting views of what they perceive friends and family to value compared to their perception of what academic staff value. Conclusions: It was recommended that the undergraduate curriculum promote equal values across theory, research, and practice by integrating education in the three domains. Utility interventions are discussed as a cost‐effective way to improve task values and performance in learning domains that are not well‐valued by students.